A collection of service time probability distributions parameters study and impact in M|G|∞system busy period and busy cycle time length probability distributions - Ferreira, M. A. M. (Advances in mathematics research, 2020)
We present the problems that arise when calculating the moments of service time probability distributions for which the M|G|∞ queue system busy period and busy cycle-an idle period followed by a busy period-time length probability distributions become very easy to study, and show how to overcome them. We also, calculate the renewal function, the “peakedness,” and the “modified peakedness” for the M|G|∞ busy period and busy cycle time length in the case of those service time distributions.